Framing and dominant metaphors in the coverage of North Korea in the Australian media. Issue 4 (7th August 2016) - Dalton, Bronwen; Jung, Kyungja; Willis, Jacqueline; Bell, Markus
Abstract: Through the selective allocation of attention, framing and metaphors in covering foreign affairs and countries, media narratives often act to delegitimise, marginalise and demonise international actors. Focusing on Australian reportage of North Korea in The Australian, The Sydney Morning Herald and from the Australian Broadcasting Corporation ( ABC ) between 1 January 2010 and 31 December 2012, this paper explicates how the framing mechanisms utilised in media point to media complicity in reinforcing a negative, adversarial orientation towards North Korea. It also discusses implications for how Australians view the North Korean people, Australian–North Korean relations, and policy pertaining to Northeast Asia more broadly.